EKSPLORASI FAKTOR-FAKTOR YANG MEMENGARUHI MINAT SISWA DALAM PENGGUNAAN MOBILE-BASED ASSESSMENT - Nur Adillawati Kosim Saputri, - (2020)
Keberlangsungan penggunaan mobile-based assessment bergantung pada minat siswa untuk menggunakannya. Jika mobile-based assessment yang digunakan tidak diminati, maka kemungkinan besar mobile-based assessment tersebut tidak akan digunakan kembali. Tujuan dari penelitian ini adalah untuk mengetahui minat siswa dalam penggunaan mobile-based assessment dilihat dari faktor Content, Eficiency, Mobile Device Anxiety, User Interface, Mobile Self-Efficacy, Facilitating Condition, Perceived Playfulness, Perceived Ease of Use, Perceived Usefulness dan Behavioural Intention to Use. Model penelitian yang digunakan diadopsi dari Mobile Based Assessment Acceptance Model (MBAAM). Data dikumpulkan melalui kuesioner online dan diolah menggunakan pendekatan Partial Least Square (PLS). Terkumpul sejumlah 281 respon dari siswa di salah satu sekolah menengah kejuruan. Hasil penelitian menunjukkan Perceived Playfulness menjadi faktor yang paling berpengaruh terhadap minat siswa diikuti oleh faktor Perceived Usefulness, dan faktor Perceived Ease of Use hanya berpengaruh secara tidak langsung. Semua faktor yang diteliti memiliki pengaruh dalam kategori tinggi terhadap minat siswa. Kata Kunci: Mobile-Based Assessment, Mobile Based Assessment Acceptance Model, Technology Acceptance Model The continued use of a mobile-based assessment depends on someone's intention to use it. If the mobile-based assessment is not in demand, it is likely that the mobile-based assessment will not be reused. The purpose of this study was to determine students' intention to use mobile-based assessments seen from the factors of Content, Efficiency, Mobile Device Anxiety, User Interface, Mobile Self-Efficacy, Facilitating Conditions, Perceived Playfulness, Perceived Ease of Use, Perceived Usefulness and Behavioral Intention to Use. The research model used was adopted from the Mobile Based Assessment Acceptance Model (MBAAM). Data were collected through online questionnaire and processed using the Partial Least Square (PLS) approach. There were 281 responses from students in one vocational high school. The results showed that Perceived Playfulness was the most influencing factor on students' intention to use followed by the Perceived Usefulness factor, and the Perceived Ease of Use factor only had an indirect effect. All of the factors studied have an influence in the high category on student intention to use mobile-based assessment. Keywords: Mobile-Based Assessment, Mobile Based Assessment Acceptance Model, Technology Acceptance Model